2010
DOI: 10.1111/j.1365-2230.2010.03983.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of p-coumaric acid on erythema and pigmentation of human skin exposed to ultraviolet radiation

Abstract: These results suggest that PCA cream can reduce UV-induced erythema formation and subsequent pigmentation in human skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…This study also demonstrated that PCA topically applied in the form of cream can have beneficial effects mitigating UVB-induced inflammatory responses and injury ( Figures 5 and 6), probably due to its strong absorption of UVB radiation (Figures 1 and 3). Together with previous studies that demonstrated the antimelanogenic effects of PCA by in vitro and in vivo experiments [10][11][12][13][14][15][16], it is now suggested that PCA may attenuate not only dyspigmentation but also inflammatory reactions due to overexposure of UVB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also demonstrated that PCA topically applied in the form of cream can have beneficial effects mitigating UVB-induced inflammatory responses and injury ( Figures 5 and 6), probably due to its strong absorption of UVB radiation (Figures 1 and 3). Together with previous studies that demonstrated the antimelanogenic effects of PCA by in vitro and in vivo experiments [10][11][12][13][14][15][16], it is now suggested that PCA may attenuate not only dyspigmentation but also inflammatory reactions due to overexposure of UVB.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PCA has been observed to mitigate the cytotoxicity of UVB in human epidermal melanocytes [13]. Long-term pre-application of PCA in the form of cream has also been observed to attenuate erythema induction in animal and human skin exposed to UV [15,16]. However, UVB-shielding effect of PCA has been relatively less investigated compared to its antimelanogenic effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, the special structures of ferulic acid and p-coumaric acid, with their scavenging capacities, provide stable phenoxyl radicals which allow them to terminate free radical chain reactions. Consequently, several research groups have studied their protective effects and have shown them to be effective against UV radiation-induced skin damage (37)(38)(39), making them an important ingredient in topical UV-shielding agents, such as sunscreens. These compounds have also been shown to provide a protective effect for cardiovascular disease and related diseases, such as hypertension and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Like the cases of other bamboo species [30,31], p-CA was assumed to contribute to bioactivities of BCTE. The protective effects of p-CA against the UV-induced inflammatory responses or injury has been previously observed in cells and in vivo models [32][33][34]. We suppose that p-CA is one of the active constituents of BCTE based on the observations in the current study, but other studies reported that BCTE contained various other constituents with antioxidant properties [16,17].…”
Section: Discussionmentioning
confidence: 45%